Chitin nanowhisker aerogels - Heath, Lindy; Zhu, Lifan; Thielemans, Wim (Wiley-VCH Verlag, 2013)
Chitin nanowhiskers are structured into mesoporous aerogels by using the same benign process used previously in our group to make cellulose nanowhisker aerogels. The nanowhiskers are sonicated in water to form a hydrogel before solvent-exchange with ethanol and drying under supercritical CO2 (scCO2). Aerogels are prepared with various densities and porosities, relating directly to the initial chitin nanowhisker content. scCO2 drying enables the mesoporous network structure to be retained as well as allowing the gel to retain its initial dimensions. The chitin aerogels have low densities (0.043–0.113 g cm−3), high porosities (up to 97 %), surface areas of up to 261 m2 g−1, and mechanical properties at the high end of other reported values (modulus between 7 and 9.3 MPa). The aerogels were further characterized by using X-ray diffraction, BET analysis, electron microscopy, FTIR, and thermogravimetric analysis. Characterization showed that the rod-like crystalline nature of the nanowhiskers was retained during the aerogel production process, making the aerogel truly an assembled structure of chitin nanocrystals. These aerogels also showed the lowest reported shrinkage during drying to date, with an average shrinkage of only 4 %.